DESAIN KEMASAN SEBAGAI BRANDING PADA UMKM CLUSTER PANGAN KOTA SEMARANG - Martono Martono; Ascariena Rafinda; Mohammad Khoiruddin; Anindya Ardiansari; Ascaryan Rafinda (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2022)
The Covid-19 pandemic that has occurred since 2020 has paralyzed various sectors around the world, including the economy in Indonesia. The sudden economic downturn is still an obstacle for most Indonesians. This also has an impact on MSMEs in Indonesia. Based on observations with the Food Cluster MSMEs in the city of Semarang, it was found that MSME actors still have problems related to packaging design. There are still many of them who only rely on makeshift packaging without any prior planning. Packaging has a vital role in branding a product. Seeing this, it is necessary to conduct packaging design training, from planning to product packaging design. After conducting packaging design training for MSMEs in the Food Cluster in the city of Semarang, MSMEs realized that several things must be considered, including the target market, packaging accuracy, easy packaging access, and attention to the suitable materials for their products. After participating in this training, MSMEs realized that packaging is not something they can underestimate because they can do branding from packaging. After all, the packaging is the first thing that consumers see.